TEACHING ENGLISH AS A FOREIGN LANGUAGE AT ELEVENTH GRADE USING ACTIVE KNOWLEDGE SHARING (AKS) STRATEGY - Sawitry, Maryanti (Linguistic, English Education and Art (LEEA) Journal, 2025)
Active knowledge sharing (AKS) is one of the active learning strategies that encourages students to be active in discussing their knowledge as the process of learning English as a foreign language. It is used for enhancing students' abilities in reading and speaking comprehension. This research was conducted to investigate how active knowledge sharing can be used by the teacher in the English classroom. The researcher collaborated with the teacher conducting the learning process in a class by using a classroom action research design; it used three cycles in implementing the strategy while teaching narrative text in an English class. Each cycle included four stages: plan, act, observe, and reflect. The data were obtained qualitatively and quantitatively. Qualitatively, the data used students’ and teachers' notes about the class activity, which became a reflection for the researcher in revising the next cycle. Students' achievement in the reading test was the quantitative data. The research showed some improvements in students’ speaking participation in discussions, students’ reading achievement, and students’ vocabulary acquisition.   Keywords: narrative text, active knowledge sharing, reading and speaking comprehension